Enhancing cognitive control in amnestic mild cognitive impairment via at-home non-invasive neuromodulation in a randomized trial - Kevin T. Jones; Avery E. Ostrand; Adam Gazzaley; Theodore P. Zanto (Scientific Reports, 2023)
Abstract Individuals with multi-domain amnestic mild cognitive impairment (md-aMCI) have an elevated risk of dementia and need interventions that may retain or remediate cognitive function. In a feasibility pilot study, 30 older adults aged 60–80 years with md-aMCI were randomized to 8 sessions of transcranial alternating current stimulation (tACS) with simultaneous cognitive control training (CCT). The intervention took place within the participant’s home without direct researcher assistance. Half of the participants received prefrontal theta tACS during CCT and the other half received control tACS. We observed high tolerability and adherence for at-home tACS + CCT. Within 1-week, only those who received theta tACS exhibited improved attentional abilities. Neuromodulation is feasible for in-home settings, which can be conducted by the patient, thereby enabling treatment in difficult to reach populations. TACS with CCT may facilitate cognitive control abilities in md-aMCI, but research in a larger population is needed to validate efficacy.